Diversity of anchovy migration patterns in an European temperate estuary and in its adjacent coastal area: implications for fishery management - Morais, P. (2013)
This study aims to study the diversity of the migration patterns of the anchovy Engraulis encrasicolus (L.,1758) collected in the Guadiana estuary (SE-Portugal/SW-Spain) and in the adjacent coastal area, by analysing Sr concentration distribution in sagittal otoliths. The distribution of Sr in otoliths of anchovy captured in the estuary allowed us to identify two major patterns: a) fish that do not migrate through estuarine salinity gradients and b) fish that make differential use of the estuary throughout their lives, occupying areas of lower salinity during the early stages of the life cycle followed by migrations to areas of higher salinity later in life. The patterns for fish captured in coastal areas inferred that they probably hatched in an estuarine environment and progressively migrated along an estuary to the coast. There is no massive migration of coastal anchovy to spawn in the estuary, as previously suggested. These results suggest that fishery managers should evaluate the contribution of estuarine populations to coastal stocks and the impact of estuarine recruitment fluctuations on this stock.